LabPipe: an extensible bioinformatics toolkit to manage experimental data and metadata - Bo Zhao; Luke Bryant; Rebecca Cordell; Michael Wilde; Dahlia Salman; Dorota Ruszkiewicz; Wadah Ibrahim; Amisha Singapuri; Tim Coats; Erol Gaillard; Caroline Beardsmore; Toru Suzuki; et al. (BMC Bioinformatics, 2020)
Abstract Background Data handling in clinical bioinformatics is often inadequate. No freely available tools provide straightforward approaches for consistent, flexible metadata collection and linkage of related experimental data generated locally by vendor software. Results To address this problem, we created LabPipe, a flexible toolkit which is driven through a local client that runs alongside vendor software and connects to a light-weight server. The toolkit allows re-usable configurations to be defined for experiment metadata and local data collection, and handles metadata entry and linkage of data. LabPipe was piloted in a multi-site clinical breathomics study. Conclusions LabPipe provided a consistent, controlled approach for handling metadata and experimental data collection, collation and linkage in the exemplar study and was flexible enough to deal effectively with different data handling challenges.